A Review of Motion Sensors as a Home Security System and approach to the Internet of Things Project - Lesmana, Yandri; Pane, Rahmadani; Hsb, Elysa Rohayani; Hakim, Lukman; Agusti, Nelly; Irmayani, Deci; adi, Puput Dani Prasetyo (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Home security is an essential factor and must be maintained; currently, the development of technology or security systems continues to be improved, one of which is Eye Retina and Artificial Intelligence. in this research, the use of Motion Sensors in Home Security, performance evaluation, and future development. In this time, more crimes occur in our environment, one of which is theft or breaking into people's homes in various areas; this problem is disturbing to residents in areas where these crimes often occur, even though so far, residents have used many methods to prevent crime, one of which is installing CCTV. However, thieves still have managed to escape the CCTV surveillance. But suppose we use a security system that can make a sound. In that case, the sound can make criminals cancel their intention to steal because the sound disturbs their concentration and can also wake the house owner or tell residents about a crime in the house. And in this article, I will describe a home security system. This system requires several supporting equipment, such as PIR, Arduino, Buzzer, and other tools.